2013
DOI: 10.1093/pcp/pct111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of Novel Bluer-Colored Chrysanthemums Produced by Accumulation of Delphinidin-Based Anthocyanins

Abstract: Chrysanthemums (Chrysanthemum morifolium Ramat.) have no purple-, violet- or blue-flowered cultivars because they lack delphinidin-based anthocyanins. This deficiency is due to the absence of the flavonoid 3',5'-hydroxylase gene (F3'5'H), which encodes the key enzyme for delphinidin biosynthesis. In F3'5'H-transformed chrysanthemums, unpredictable and unstable expression levels have hampered successful production of delphinidin and reduced desired changes in flower color. With the aim of achieving delphinidin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 28 publications
1
70
0
2
Order By: Relevance
“…Increased delphinidin levels (up to 80%) were further achieved by hairpin RNA interference-mediated silencing of the endogenous F3H gene and the resulting petal colours were novel bluish hues. Blue pigmentation in petals of chrysanthemum has also been reported by Noda et al 61 through generation of delphinidin-based anthocyanins by expression of the flavonoid 3,5-hydroxylase gene. Huang et al 62 also used RNAi technology to induce red and blue flowers in C. morifolium by downregulating CmF3H (flavanone 3-hydroxylase gene hydroxylated at the 3-position) and overexpressing the Senecio cruentus F35H (PCFH) (flavanone 3-hydroxylase gene hydroxylated at the 3-and 5-positions) gene in chrysanthemum.…”
Section: Chrysanthemum (Dendranthema Grandiflora)supporting
confidence: 67%
“…Increased delphinidin levels (up to 80%) were further achieved by hairpin RNA interference-mediated silencing of the endogenous F3H gene and the resulting petal colours were novel bluish hues. Blue pigmentation in petals of chrysanthemum has also been reported by Noda et al 61 through generation of delphinidin-based anthocyanins by expression of the flavonoid 3,5-hydroxylase gene. Huang et al 62 also used RNAi technology to induce red and blue flowers in C. morifolium by downregulating CmF3H (flavanone 3-hydroxylase gene hydroxylated at the 3-position) and overexpressing the Senecio cruentus F35H (PCFH) (flavanone 3-hydroxylase gene hydroxylated at the 3-and 5-positions) gene in chrysanthemum.…”
Section: Chrysanthemum (Dendranthema Grandiflora)supporting
confidence: 67%
“…According to previous studies, flower color is an important factor in pollination and plant reproduction by attracting pollinators (Brown and Clegg 1984;Jones and Reithel 2001;Noda et al 2013) and affecting the behavior of herbivores, which discriminate against or prefer certain color morphs (Simms and Bucher 1996;Irwin et al 2003;Caruso et al 2010). Flower pigments are also related to disease defense and UV protection (Koes et al 1994;Treutter 2005).…”
Section: Introductionmentioning
confidence: 99%
“…F3959H activities enable plants to synthesize delphinidin-based anthocyanins, which confer violet/ blue color in flowers and fruits, potentially a selective advantage in angiosperms for attraction of pollinators and seed dispersers (Harborne, 2014). A number of dicot F3959H genes have been isolated for engineering flower colors in plants without violet/blue pigmentation, such as roses (Rosa hybrida; Katsumoto et al, 2007), chrysanthemums (Chrysanthemum morifolium; Brugliera et al, 2013;Noda et al, 2013), and carnations (Dianthus caryophyllus; Tanaka and Brugliera, 2013). On the other hand, suppression of F3959H expression in torenia (Torenia hybrida; Suzuki et al, 2000) and cyclamen (Cyclamen persicum; Boase et al, 2010) was shown to shift the petal colors from violet/blue to red.…”
mentioning
confidence: 99%